Carl Menger's Smithian contributions to German political economy - Stefan Kolev; Erwin Dekker (The Review of Austrian Economics, 2022)
In this paper we contextualize Carl Menger's work in relation to the transformations of German political economy from the 1860s to the 1890s. We demonstrate that his Grundsätze ( 49 ) was a culmination of the German subjectivist tradition which had started in the early nineteenth century. Menger's synthesis of this tradition is comparable to Adam Smith's synthesis of earlier knowledge in the Wealth of Nations ( 68 ). Menger's contribution was continuous with the intellectual project of leading German economists, such as Wilhelm Roscher, to whom Menger had dedicated his book. Roscher, however, also promoted a historical turn, that was~combined with a progressive~policy agenda by a new generation of German economists after they founded the Verein für Socialpolitik in 1872. These divergent Roscherian legacies clashed vehemently in the Methodenstreit. During this debate Menger elaborated in his Untersuchungen ( 50 ) an evolutionary and spontaneous theory of institutional change, in line with the legacy of the Scottish Enlightenment and in contrast to a more rationalist and constructivist theory of institutional change expounded by Gustav Schmoller and other Verein economists. The new policy-oriented direction of German political economy carried the day, also due the fundamental socio-economic transformations in the German and Austro-Hungarian Empires, and prompted Menger to restate in 1891 the social policy agenda of the classical political economists, most prominently Smith. Menger's recurrent proximities to Smithian political economy – in the synthetic contribution of 1871, the theoretical innovation of 1883, and the policy agenda of 1891 – suggest that his arguments are best understood as a defense of what Boettke has called the "mainline" in economics.
Keywords: A11; B12; B15; B53; P16; 330; Carl Menger; Adam Smith; Methodenstreit; Social Policy; Mainline Economics